Metabolite Profiling Differences of Single and Physical Mixture of Moringa Leaves (Moringa oleifera) and Red Galangal (Alpinia purpurata (Vieill) K. Schum) - Martina Simbolon; Rimbawan Rimbawan; Kartin Roosita; I Made Artika (Media Publikasi Cendekia Indonesia, 2026)
econdary metabolites are bioactive plant constituents that contribute to antioxidant, anti-inflammatory, and anti-microbial activities, making them valuable for functional food and nutraceuticals applications. This study aimed to characterize the secondary metabolites present in powdered Moringa oleifera leaves, red galangal (Alpinia purpurata (Vieill) K. Schum) rhizomes, and their combination. The 85:15 ratio used in the mixed powder was selected based on preliminary material composition considerations. Metabolite identification was conducted using Ultra High Performance Liquid Chromatography Tandem High Resolution Mass Spectrometry (UHPLC-HRMS). Data processing and compound annotation were performed using ChemSpider and mzCloud. A total of 21 metabolites were identified in moringa leaf powder, 16 compounds in red galangal rhizome, and 17 compounds in the combined preparation. Flavonoid were the dominant class in moringa leaves with quercitrin, 4-aminobenzoid acids, and pheophorbide A as the most abundant constituents. In contrast, phenolic compounds, particularly benzoic derivatives were predominant in red galangal, where menadiol, abietin, and sweroside were the major metabolites. The combined formulation retained key constituents from both plants, including cinnamaldehyde, 4-aminobenzoic acid, and pheophorbide A, and additionally showed an increased level of nictoflorin. These findings provide preliminary compositional evidence demostrating the distinct and complementary phytochemical profiles of moringa leaves and red galangal rhizomes. This information may guide future studies into potential functional food or nutraceutical formulations for further validation through bioactivity, bioavailability, and interaction studies.